Narrative review of ferroptosis in obesity - He, Lian‐Ping; Zhou, Zi‐Xuan; Li, Cui‐Ping (Journal of cellular and molecular medicine, 2023)
Obesity is widely recognized as a major global health problem caused by a chronic energy imbalance resulting from a combination of excess caloric intake and insufficient energy expenditure. Excessive energy intake and physical inactivity are traditional risk factors for obesity. Obesity is a risk factor for many diseases, including hypertension, diabetes and tumours. Recent studies have found a strong link between ferroptosis and obesity. Ferroptosis is an iron‐dependent regulated cell death caused by iron overload and reactive oxygen species‐dependent excessive accumulation of lipid peroxidation. Ferroptosis is involved in many biological processes, such as amino acid metabolism, iron metabolism and lipid metabolism. Some potential strategies to reduce the adverse effects of ferroptosis on obesity are suggested and future research priorities are highlighted.